Troubled IT projects prevention and turnaround - Smith, John M. 1947- (Institution of Engineering and Technology, 2001)
Many IT projects are doomed before the ink is dry on the contract. In this highly readable book, John Smith sets out the 40 root causes of troubled IT projects and explains how these can be avoided at each stage of the project life cycle. The coverage of opportunity management, solution generation and proposal generation will help IT services Vendors increase sales and buyers become more effective at proposal evaluation. A proven approach to reviewing projects in delivery is presented to ensure that projects stay on track. The book goes on to describe an approach to 'turning around' a troubled project. Key to this- and a theme throughout the book- is the achievement of a high level of engagement and trust between Vendor and Buyer.